Scroll or Stuck: Uncovering Fear of Missing Out (FOMO) Among Public Relations Students - Anisa Oktafriani; Yanti Dwi Astuti (Interaksi: Jurnal Ilmu Komunikasi, 2025)
This study aims to explore the lived experiences and meaning-making of FoMO among members of the PERHUMAS Muda Yogyakarta 2023 cohort, a public relations student organization that paradoxically possesses strategic communication awareness yet remains vulnerable to FoMO. Using a qualitative approach with Interpretative Phenomenological Analysis (IPA) and the Self-Determination Theory (SDT) framework, data were collected through in-depth interviews, observation, and documentation involving four informants. Findings reveal that FoMO is not merely a fear of missing out, but a manifestation of efforts to fulfill three basic psychological needs: (1) Autonomy, in which FoMO drives digital identity management strategies through account separation (first/second account); (2) Competence, in which FoMO acts as a double-edged catalyst, simultaneously triggering social comparison anxiety while driving productive behaviors such as participation in competitions; and (3) Relatedness, which creates a paradox of being "digitally connected but relationally empty." The novelty of this research lies in unpacking the duality of FoMO as both a pathology and a professional catalyst, as well as the discovery of impression management strategies as an autonomous response to digital pressure. Theoretical and practical implications for communication education and digital mental health are discussed.